Management Of Preservation Of The Rejang Dance As An Intangible Cultural Heritage Of The Province Of Bali - Puspawati, Gusti Ayu Made; Hartono; Purnomo, Sucipto Hadi (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2025)
This research examines the management of preserving traditional Balinese arts, especially the Rejang Dance, which was developed and preserved by the Balinese people. The aim of the research is to understand the form of management carried out by the community in an effort to preserve the Rejang dance in Bali. In this research, the method used is descriptive qualitative and data collection through observation, interviews and documentation. Meanwhile, the results of this research provide various forms of conservation management such as; (1) history of Rejang dance; (2) supporting factors for Rejang dance performances, as well as (3) management efforts to preserve Rejang dance. Management of Rejang Dance performances by the Balinese people includes maintaining the musical instruments that accompany Rejang dance performances (gamelan), consistency in maintaining traditions, readiness for performances in traditional and modern realms, as well as collaborative innovation with other musical performances. In conclusion, efforts to preserve the Rejang Dance involve various parties and strategies, creating continuity of traditional culture in Bali.